1996
DOI: 10.1111/j.1476-5381.1996.tb15702.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 5‐HT and selective 5‐HT receptor agonists and antagonists on rat dorsal vagal preganglionic neurones in vitro

Abstract: 1 Whole-cell patch-clamp recordings were made from 142 visually identified rat dorsal vagal preganglionic neurones (DVMs). Applications of 5-hydroxytryptamine (5-HT, 20 guM, 2 min) elicited a slow depolarization (8.2 + 0.5 mV, n = 59) in 95% of the cells tested, accompanied by an increase in excitability. In (68%) of DVMs the depolarization was associated with an increase in apparent membrane resistance (Rm, 22.7+2.2%). These depolarizations and increases in Rm (14.3+2.6%, n=8) were maintained in a medium whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…The result that application of the antibody to TASK-3 blocked 5-HT-induced depolarization in interneurons suggests that 5-HT increases GABA release via inhibition of TASK-3 channels. Consistent with our results, TASK-3 channels are expressed in interneurons (Berg and Bayliss, 2007; Torborg et al, 2006) and inhibited by Gq-coupled receptors (Chen et al, 2006; Veale et al, 2007; Mathie, 2007) including 5-HT 2A receptors (Albert et al, 1996; Browning and Travagli, 1999; Hopwood and Trapp, 2005). …”
Section: Discussionsupporting
confidence: 92%
“…The result that application of the antibody to TASK-3 blocked 5-HT-induced depolarization in interneurons suggests that 5-HT increases GABA release via inhibition of TASK-3 channels. Consistent with our results, TASK-3 channels are expressed in interneurons (Berg and Bayliss, 2007; Torborg et al, 2006) and inhibited by Gq-coupled receptors (Chen et al, 2006; Veale et al, 2007; Mathie, 2007) including 5-HT 2A receptors (Albert et al, 1996; Browning and Travagli, 1999; Hopwood and Trapp, 2005). …”
Section: Discussionsupporting
confidence: 92%
“…Immunohistochemical studies showed a high density of TRH-immunoreactive fibers within the DVC (236, 310) that were eliminated following transection of the pathway from the medullary raphe nuclei to the DVC (364). Medullary raphe neurons have also been shown to contain and release 5-HT and substance P which have also been implicated in modulation of gastric functions including motility and secretion (273, 464, 476, 477) via actions at DVC neurons (7, 75, 76, 292, 378, 532). …”
Section: Cns Regulation Of Sympathetic and Parasympathetic Control Ofmentioning
confidence: 99%
“…The response to pharmacological stimuli of DMV neurones is even more complex when 5-HT is analysed. Studies conducted by various groups have shown that discrete subsets of DMV neurones show diverse responses to exogenous application of 5-HT through actions at different receptor subtypes (Travagli & Gillis, 1995;Yoneda & Tache, 1995;Albert et al 1996;Wang et al 1996Wang et al , 1997Wang et al , 1998. It is proposed that such non-uniformity of response of DMV neurones to application of exogenous neurotransmitters may reflect differences in their complement of voltage-dependent currents as well as receptor binding sites.…”
Section: Electrophysiological Differences In Dmv Neuronal Subgroupsmentioning
confidence: 99%